Community structure of fiddler crabs (Uca spp.) in the mangrove ecosystem in the Sungai Rawa, Sungai Apit Sub-district, Siak District - Musdalifah Desti Andini; Adriman Adriman; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTFiddler crabs (Uca spp.) is a type of crab that lives in the mangrove ecosystem. The presence of illegal logging and domestic activities affect the mangrove ecosystem as well as related organisms, including fiddler crabs. This research aims to understand the structure of crab community (Uca spp.) in the mangrove ecosystem of Sungai Rawa, and it was conducted on March 2018. The fiddler crab samples were collected from 3 plots (1m x 1m) placed along the transect line. Crabs in the plot are collected manually, three times, once/ week. Results shown that there were 4 species of fiddler crab, namely Uca jocelynae, Uca dussumieri, Uca triangularis and Uca vocans.Among these species, the most abundant was Uca dussumieri. The crab abundance ranged from 22,963 to 88,519 organisms/ha. The value of diversity index was (H’) 1,514-1,974 the dominace index was (C) 0.259-0.368 and the uniformity index was (E) 0.955-0.987, the water quality parameters are as follows : temperature was 28-30 oC; pH was 7.3-7.7; salinity was 28-31‰ and disolved oxygen was 5.1-6.2 mg/L.Key words: Crab community, Uca dussumieri, Mangrove ecosystem, Mangrove organism